From: D 1133/1 fol. Cemetary of Friedrichsfelde in Berlin. Statue for Luxemburg, Liebknecht and their companions
From: D 1133/1 fol. Cemetary of Friedrichsfelde in Berlin. Statue for Luxemburg, Liebknecht and their companions.